Crocodiles, pallettari, limeurs and arrotini: The Cultural Charge of the Slang Terms of the Tennis Lexicon in French and Italian Sports Dictionaries - Emanuele, Valerio (Verbum, 2022)
In this article, we undertake a contrastive analysis of some slang words and expressions of the tennis lexicon in French and Italian. Using the notion of "lexiculture", coined by Robert Galisson, we will adopt - on the basis of a corpus of dictionaries of sports and sports slang in both languages - a comparative approach, reviewing some "culturally charged" terminological entries relating to the French and Italian tennis lexicon. Through this approach, we aim not only to bring out the culture sedimented in the selected lexical units, but also to show how these cultural references — being often specific to the idiom and civilization in which these slang lexical units were forged — pose many difficulties when translating.